2022
DOI: 10.48550/arxiv.2202.01886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the abnormal temperature dependent elastic properties of fused silica irradiated by ultrafast lasers

Abstract: Materials with thermal-invariant elastic properties of materials are of interest for resonant device frequency and dimensional stability of precision devices. Here, we demonstrate that the temperature coefficient of elasticity (TCE) of amorphous silica can be locally reduced using femtosecond laser irradiation. Notably, a self-organized laser-induced modification shows a decrease of the TCE beyond 50%. The origin of this dramatic decrease is attributed to the presence of sub-micron permanent densified zones wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…It was also found that the densification inside the laser affected zone (LAZ) is higher than the densification due to homogeneous modification, a densification exposure regime found at shorter pulse duration and lower pulse energy 28 . Using the same method proposed by 22 and used for a the first estimate of the pressure in between the beams, we estimated a pressure approaching 15 GPa, see Fig 6.This estimate is based on the assumption of an hydrostatic pressure and therefore, most likely underestimates what the real pressure was, as the loading case is present for a short duration and.…”
Section: Modification Along the Laser Affected Zonementioning
confidence: 99%
“…It was also found that the densification inside the laser affected zone (LAZ) is higher than the densification due to homogeneous modification, a densification exposure regime found at shorter pulse duration and lower pulse energy 28 . Using the same method proposed by 22 and used for a the first estimate of the pressure in between the beams, we estimated a pressure approaching 15 GPa, see Fig 6.This estimate is based on the assumption of an hydrostatic pressure and therefore, most likely underestimates what the real pressure was, as the loading case is present for a short duration and.…”
Section: Modification Along the Laser Affected Zonementioning
confidence: 99%